Effects of forest fire on wood: a biological (anatomical study) - Budi, A.S. (Center for International Forestry Research, 2001)
The effects of forest fire on wood were studied on fifteen dead and living trees of various tropical species. The wood reacted in the following ways: (1) creating smaller but denser pores than normal in a concentric pattern, (2) changing dimension and numbers of axial parenchyma, (3) producing more axial intercellular canals, (4) forming decay spots in the wood, (5) creating the concentric area of fibres area or forming the vessels late, (6) creating new calluses and the bole losing its cylindrical form, (7) producing abnormal gums in the wood and (8) the bole becoming hollow. These abnormalities decrease physical or mechanical properties depending on how serious the defect is in the wood. Wood deterioration was more strongly influenced by the conditions caused by the forest fire and subsequent attacks by fungus, bacteria and insects than by fire itself. There were various effects depending on the durability and other properties of the wood. The wood was classified into four groups: “merkubung/sengon”, “akasia/medang”, “ulin” and “leda”, according to condition in the field.